BENCANA DAN PERUBAHAN IDENTITAS DESA BULAK 1971-2000an - Muhammad Alfan Jazli; Emy Wuryani (Unit Penelitian dan Publikasi Fakultas Ilmu Budaya Universitas Gadjah Mada, 2020)
This article discusses the history of the disaster that struck the Bulak Village in the area of Jepara, Central Java, Indonesia in the 1971-2000s period. Disasters that continue to occur in the village of Bulak force villagers to move to the new village location. The new village was named after Desa Bulak Baru as a sign that the name of Desa Bulak Baru was not part of the expansion of the old village, but as a collective memory of the name of their previous village. To see that change, the writer sees it in the lens of migration in the local definition, namely village bedol. Bedol Desa is a term for the people of the villages in Java who migrate. The study of village bedol events in the perspective of social history studies. In 1981 a village bedol event occurred in Bulak Village, Jepara Regency. The destination of the bedol desa is the location Desa Bulak Baru. Naming that includes a change of identity, but does not eliminate the old name as the historical basis of a Bulak Village. The method used in this study is the historical method, which includes: (1) heuristics or source tracking, (2) source criticism to verify the information obtained, (3) analysis, and (4) historiography or historical writing.